The government regulation of medical services (Journal of Economic Research & Business Administration, 2015)
This article has the theoretical positions of national and regional health by legislation in the Republic of Kazakhstan. As well, the current state of medical institutions in developed countries in the field of health care.
Keywords: financial - economic performance; health and social care; rising costs; intensive migration; the insurance system; the regional market.